A New PNA-FISH Probe Targeting Fannyhessea vaginae - Sousa, Lúcia G. V.; Castro, Joana; França, Angela; Almeida, Carina; Muzny, Christina A.; Cerca, Nuno (Frontiers in Cellular and Infection Microbiology, 2021)
Bacterial vaginosis (BV) is the most common vaginal infection in women of reproductive age and has been associated with serious health complications, mainly in pregnant women. It is characterized by a decrease in the number of Lactobacillus species in the healthy vaginal microbiota and an overgrowth of strict and facultative anaerobic bacteria that develop a polymicrobial biofilm. Despite over 60 years of research investigating BV, its etiology is not fully understood. Gardnerella spp. is a crucial microorganism that contributes to the formation of the biofilm and the development of BV, but the role of other BV-associated bacteria is not clear. Nevertheless, Fannyhessea vaginae (previously known as Atopobium vaginae) is a highly specific species for BV, and co-colonization with Gardnerella is thought to be a very specific diagnostic marker. The diagnosis of BV still presents some limitations, since currently used methods often fail to accurately detect BV. This work aims to develop a novel peptide nucleic acid (PNA) probe targeting F. vaginae. This probe was further validated in a multiplex assay, which included a Gardnerella-specific PNA probe, as a possible method for diagnosis of BV, and was compared with quantification by qPCR. The new PNA probe showed excellent sensitivity and specificity and could discriminate F. vaginae-Gardnerella biofilms, confirming the potential to be used for the detection of BV-associated pathogens.